Reconciling phylogenetic and morphological trends in North American Mammuthus. (2nd July 2017) - Widga, Chris; Saunders, Jeff; Enk, Jacob
Abstract: The morphology of mammoth upper third permanent molars (M3) is used to address regional- and continental-scale patterns in the structure of mammoth populations. Recent refinements to the understanding of Mammuthus phylogenetic diversity south of the Laurentide ice show extensive overlap between regional populations. We assess the underlying geographic structure in Mammuthus tooth morphology in light of these new genetic data. Comparison of regional trends in dental morphology show a single, morphologically variable, population of Mammuthus was present in North America during the Wisconsin glaciation. Within this population, there are no significant differences in degree of hypsodonty or molar shape however, there is a geographic pattern of lower enamel:dentin ratios in Mammuthus from the Channel Islands, West Coast, and Southwest/Mexico as measured by the number of molar lamellae and the standardized thickness of lamellae. These results contrast with historical perspectives of Mammuthus population structure suggesting at least four species of North American mammoths but are consistent with recent phylogeographic analyses of mitochondrial ancient DNA.